Perinatal Hypophosphatasia in a Premature Infant - Sankaran, Deepika; Chandrasekharan, Praveen K.; Rawat, Munmun (American Journal of Perinatology Reports, 2020)
A premature male infant was delivered at 32 weeks' gestation due to category-2 fetal tracing after preterm labor. The physical exam showed shortened and bowed long bones, with calvarium felt in small area of the head. Serum alkaline phosphatase was very low on admission. Extensive metaphyseal abnormalities, bowing of long bones, and poor ossification of all bones were noted on skeletal survey (radiography). Based on ultrasound evidence of “bowing” and long bone fractures at 26 weeks, amniocentesis was performed that later diagnosed hypophosphatasia by genetic testing while ruling out osteogenesis imperfecta. Although ventilated initially, the infant gradually improved with enzyme replacement therapy (ERT) and was extubated to noninvasive ventilation for 6 weeks. Following clinical deterioration with hypoxic respiratory failure secondary to sepsis at 4 months of age, he succumbed to severe pulmonary hypertension, likely secondary to chronic lung disease and prolonged ventilation. Early diagnosis allowed timely initiation of appropriate therapy. Radiological improvement with the therapy showed promising results in this rare disease. Despite specific novel therapy being available, variability in presentation dictates prognosis in this previously universally fatal condition. The potential unknown effects of ERT on pulmonary vascular remodeling need further investigation.
Keywords: hypophosphatasia; ossification; alkaline phosphatase